Fighting corruption How the Communist Party of China works - Xie Chuntao (Singapore Cengage Asia, 2019)
The book highlights the CPC’s fight against corruption to ensure proper governance for the people of China. The reform and achievements of the disciplinary inspection system show how the CPC is building a clean government. Readers will see how power is supervised in the government to improve Party conduct.
Chapter 1 Commitment to Improving Party Conduct, Upholding Integrity and Combating Corruption.
Chapter 2 Carrying Out the ‘Eight Rules’
Chapter 3 Zero Tolerance for Corruption: Catching Both ‘Flies’ and ‘Tigers’.
Chapter 4 Power Must Be ‘Caged’ by the System
Chapter 5 The CPC’s Discipline Inspection System: an Efficient Tool Against Corruption
Keywords: Political corruption -- China -- Prevention; Criminal justice, Administration of -- Political aspects -- China